A novel application of pre-signals to improve the performance of signalized intersections: Evaluation through simulation - Vieira, António Amaro Costa (2019)
To ponder less costlier solutions to solve traffic congestion problems at signalized intersections, this paper proposes a novel application consisting of using pre-signals. Hence, an agent-based traffic simulation model was developed, where it is possible to model different types of intersections - including roundabouts of different sizes - and quantify and compare their performance. By analyzing the simulation results, it was found that: on the intersection with pre-signals, an increase in the flow of 10% and 3% was registered, the vehicles spent 1 and 2 less minutes to cross the intersection and the fuel consumption was decreased in 22% and 44%, in comparison to regular intersections and roundabouts, respectively. Concerning the size of queues, it was noted that the queues of the regular intersection were 60 meters longer than the queues on the intersection with pre-signals and on the roundabout. Based on these findings, and by making cost assumptions, a small cost analysis was made, which indicates that at least 1 million € could be yearly saved.